Audience Reception of Gender Injustice in The Drama Series “Gadis Kretek” - Rahmawati, Yeni; Romadani, Anggit Tiyas Fitra; Hidayat, Rahmat (LITERATUR : Jurnal Bahasa dan Sastra, 2025)
This study aims to determine the various audience receptions of gender injustice in the drama series "Gadis Kretek". The forms of gender injustice discussed in this study are marginalization, subordination, stereotypes, and violence. Reception data were collected through questionnaires and analyzed based on literary reception methods. The object of this study is the drama series "Gadis Kretek" which is broadcast on the Netflix application. The subjects of this study were all viewers of the drama series "Gadis Kretek". Data collection techniques, namely observation, questionnaires, and documentation. Data analysis techniques in this study, namely recording the respondent's answer scores, tabulating the respondent's answers, finding the percentage, and interpreting the percentage results. The results of this study show that of the twelve statements in the questionnaire, the results obtained were that the most dominant statements were of agreement. The most statements of agreement are found in statements 4, 6, and 7, namely 26 (9%). Meanwhile, the fewest statements of agreement are found in statement 1, namely 20 (7%). This study shows that the audience has a fairly high awareness of gender inequality issues presented in visual literary works. This can be a basis for content creators and educators to further utilize popular media as an educational tool in fostering critical awareness of gender issues in society.